Development strategy of Kuala Tadu Fish Landing, Tadu Raya District, Nagan Raya Regency - Hafinuddin, Hafinuddin; Junaidi, Habib; Thahir, Muhammad Agam; Ukhty, Nabila (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Kuala Tadu Fish Landing Base (FLB) is one of the fishing ports located in Kuala Tadu Village, Tadu Raya District, Nagan Raya Regency, Aceh Province, which plays an important role in the local fishermen's economy, which is managed under the Maritime Fisheries and Food Service (MFFS) Nagan Raya. For now, the Kuala Tadu fish landing base is still not functioning properly, so there is a need for a development process for the fishing port. This study aims to formulate a strategy for developing an appropriate Kuala Tadu fish landing base. This research uses observation and interview methods, using 15 samples, were analyzed using SWOT analysis. The strategy obtained for the development of PPI Kuala Tadu employs quadrant III (WO strategy), indicating that PPI Kuala Tadu has several opportunities but requires an approach to minimize internal issues. Therefore, the proposed strategy includes efforts to improve internal port infrastructure, such as refining the supply of clean water, upgrading sanitation facilities, enhancing drainage systems, and refurbishing administrative buildings. Additionally, initiatives can be taken to increase fishermen's knowledge of capture fisheries, expand PPI land areas, improve the functions of the Fish Marketing Place (TPI) and provide functional facilities such as ice factories or cold storage.